Psychoemotional stability - Elena N. Sorokina; Alena Yu. Gura; Irina N. Ron (Revista on line de Política e Gestão Educacional)
This study aims to consider educational conditions for the formation of psychoemotional stability of student-athletes for competitive events in dance sports in a university environment. This article also attempts to make a theoretical analysis of the formation of psychoemotional stability, the impact on the educational and training process, and the result of competitive activity on the basis of teaching aids and firsthand knowledge. To meet the study’s aims, theoretical analysis, and systematization methods are utilized. The results obtained demonstrate the pedagogical importance of the formation of psychoemotional stability of athletes at the stage of improving sportsmanship to contest and competition activities in dance sports, its influence on the educational and training process, and the quality of performance under conditions of vigorous competitive stress has been revealed.